Pengaruh Lingkungan Kerja dan Kepemimpinan Terhadap Kinerja Karyawan Melalui Kepuasan Kerja - Diski Setiawan; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Epsilon Journal of Management, 2024)
The purpose of this study is to determine the influence of the work environment and leadership on employee performance through job satisfaction. This type of research uses quantitative research methods with descriptive analysis. The data collection method used was a questionnaire measured on a Likert scale ranging from 1-5. The data analysis techniques used in this study are: Outer Model with Convergent Reliability, Composite Reliability, Cronbach's Alpha and Inner Model calculations with T statistic, R-Square, f-Square, and VIF calculations using SmartPLS (Partial Least Square) tools version 4.0.9.3. The results showed that: 1) There is a direct positive and significant influence between the work environment on job satisfaction. 2) There is a direct positive and significant influence between the work environment on employee performance. 3) There is a direct positive and significant influence between leadership and job satisfaction. 4) There is a direct positive and significant influence between leadership on employee performance. 5) There is a direct positive and significant influence between job satisfaction and employee performance.